Evaluation of functional outcome in patients treated with locking compression plate for distal femur fractures - Kevin Sebastian; Dr Sanoj P. Poulose; Dr. Akhil K. Thomas; Dr. Shery Valsan (Journal of the Bulgarian Orthopaedics and Trauma Association)
Distal femur fractures are always a challenge to an orthopedic surgeon. They may be unstable and comminuted. Thin cortex, wide medullary canal, relative osteopenia and short distal segment adds to the complexity. The present study assessed the functional outcome of using locking compression plate fixation for fractures of distal end of femur in patients admitted to JMMC orthopedics department satisfying the inclusion and exclusion criteria from December 2017 to may 2019. Twenty cases were taken in this study. Serial follow up was done at 4, 8, 12, 24 weeks and functional outcome was assessed at the end of 24 weeks using NEERS criteria. 18 patients were treated with open reduction and internal fixation. 2 of the fractures were stabilized via MIPPO technique. No patients had implant failure and none of the cases were complicated by deep infection. 5 of the 20 patients had ‘Excellent’ Neers scores and 14 had ‘Good’ scores. Only one patient had ‘Fair’ score.